The Role Of Husbands And Midwives' Motivation For Compliance With Providing Informed Consent In Cito Sc Actions At Merauke Regional Hospital - Hermin Langdo Layuk; Reny Yuli Astutik; Eri Puji Kumalasari; Devy Putri Nursanti (Journal of Health Science Community, 2024)
Informed consent is a critical aspect of medical practice, including emergency caesarean section (SC) or Cito. Compliance with informed consent becomes more complex because it involves quick decisions in emergency situations, Informed consent compliance with Cito SC actions can be influenced by the husband's role and midwife's motivation. This study aims to determine the influence of the role of husbands and midwives' motivation on compliance with the provision of informed consent in cito SC actions at Merauke Regional Hospital. This study used an Observational Analytics research design with a cross sectional approach. Sampling was carried out using the total sampling technique and a sample of 15 respondents was obtained, The independent variable consists of the role of the husband and the motivation of the midwife then the dependent variable used is the adherence of giving informed consent. The Chi-Square test is used to determine the relationship between two categorical variables. The results of the study of 15 respondents were obtained, most respondents had supporting husband role criteria, namely as many as 8 respondents (53.3%), Most respondents received poor midwife motivation which was as many as 8 respondents (53.3%) and most respondents included the criteria for compliance with informed concent on Cito SC Actions. The results of the analysis using the Chi-Square statistical test obtained the results of p = 0.005 and 0.019 < 0.05, then H0 was rejected and H1 was accepted, which means that there is an influence on the role of the husband and the motivation of midwives on Compliance with Giving Informed Consent to Pregnant Women Who Perform Cito SC Actions at Merauke Regional Hospital. The role of the husband and the motivation of midwives play a very significant role in shaping the compliance of informed consent to pregnant women. Collaboration between patients, husbands, medical teams is the main key.